Fiber Optic Sensing and Imaging - Kang, Jin U.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book is designed to highlight the basic principles of fiber optic imaging and sensing devices. The editor has organized the book to provide the reader with a solid foundation in fiber optic imaging and sensing devices. It begins with an introductory chapter that starts from Maxwell$1 (Bs equations and ends with the derivation of the basic optical fiber characteristic equations and solutions (i.e. fiber modes). Chapter 2 reviews most common fiber optic interferometric devices and Chapter 3 discusses the basics of fiber optic imagers with emphasis on fiber optic confocal microscope. The fiber optic interferometric sensors are discussed in detail in chapter 4 and 5. Chapter 6 covers optical coherence tomography and goes into the details of signal processing and systems level approach of the real-time OCT implementation. Also useful forms of device characteristic equations are provided so that this book can be used as a reference for scientists and engineers in the optics and related fields.s
Optical Fibers -- Fiber Optic Interferometric Devices -- Fiber Optic Imagers -- Optical Fiber Gratings for Mechanical and Bio-sensing -- Sagnac Loop Sensors -- Principles of Optical Coherence Tomography.
Keywords: Engineering; Microwaves; Telecommunication; Engineering; Microwaves, RF and Optical Engineering; Communications Engineering, Networks; Signal, Image and Speech Processing